Assessing Diabetes Screening Outcomes in Klang Valley, Malaysia: A Cross-Sectional Study - Gauri Krishnaswamy; Reshma Mohamed Ansari; Jing Hang Ng; Chen Yekun, (Malaysian Journal of Science (MJS), 2025)
Diabetes mellitus, once primarily affecting the elderly, is now increasingly diagnosed in younger individuals due to poor lifestyle habits. Early detection through health screening is essential for effective management. A government agency that has conducted diabetes screening programs since 2013 launched its third initiative, aiming for an 80% detection rate among screened participants using HbA1c (cutoff ≥ 6.3%), rather than reflecting national diabetes prevalence. This cross-sectional study evaluated the program’s effectiveness in detecting diabetes among Malaysian adults aged 40 to 59 in Klang Valley. A total of 188 participants attended free screenings at registered clinics between September and December 2023. The cohort included 47.35% men and 52.65% women, with 41.5% Malays, 40.4% Chinese, 14.4% Indians, and 3.7% from other ethnic groups. HbA1c levels ≥ 6.3% were found in 27.12% of participants, with the highest prevalence among Indians (33.3%), followed by Malays (29%), Chinese (23.68%), and others (14.28%). Statistical analysis (ANOVA) showed no significant association between HbA1c levels and age, gender, or ethnicity (p = 0.188). The program did not meet its 80% detection target, suggesting that alternative screening approaches, including revised diagnostic criteria or additional risk assessments, may be needed to improve diabetes detection and intervention efforts.